Governance and public management :bstrategic foundations for volatile times - Conteh, Charles; Greitens, Thomas J.; Jesuit, David K.; Roberge, Ian (Routledge, Taylor & Francis Group, 2014)
This book presents the strategic foundations for government's role in fostering and adapting to societal transformation in a volatile world. It shifts the focus of the discipline from an overtly retrospective analysis to a prospective analysis, incorporating the role of foresight techniques and instruments. Above all, it stimulates debate about the practical implications of governance as an emergent future-oriented framework of public management. This challenging book aims to facilitate dialogue and discussion between academics and practitioners, and encourage advanced students to take a new perspective on Public Management during these volatile times